Teaching Pronunciation To Young Learners - Černá, Andrea (Univerzita Pardubice, 2011)
This bachelor paper aims at stressing pronunciation teaching to young learners as one of the prominent factors in gaining the communicative competence in English. Firstly, the theoretical part concentrates on young learners and their cognitive and social development, as well as the factors influencing foreign language acquisition. Secondly, the term communicative competence as the goal in English language teaching is described. The last chapter of the theoretical part deals with aspects of pronunciation. Emphasis is put on the teacher's role, as well as possible difficulties to be aware of among Czech learners. Finally, a range of techniques and activities to refine learners' pronunciation is provided. The practical part describes a small scale research aimed at investigating the situation as to how pronunciation teaching is practiced in the Czech primary schools and furthermore, what are the teachers' attitudes towards teaching pronunciation to young learners in order to achieve the communicative competence in English language.
Výuka angličtiny zaměřená na výslovnost u mladých žáků
Keywords: žáci mlašího školního věku; osvojování jazyka; komunikativní kompetence; výslovnost; young learners; language acquisition; communicative competence; pronunciation